PENERAPAN LEAN HEALTHCARE DALAM PENGELOLAAN MANAJEMEN KEPERAWATAN DI RAWAT INAP DHAHA RSUD GAMBIRAN KOTA KEDIRI - Ellina, Agusta Dian; S, Eko Dian; wuryani, Ary Dwi; Panggalih, Dangan; K, Beko; Istiqomah, Istiqomah; Baersady, Miriam; Saly, Salami; Kristina, Yuyun (PPM STIKES Adi Husada, 2023)
Introduction & aim: Lean is a new breakthrough in the era of digitalization which is a process improvement method used to improve service products, high use of consumables (hereinafter referred to as BHP) in hospitals, stock inventory of drugs and medical devices in the treatment room every month and found a buildup of inventory of consumables. This community service aimed to identify the application of lean healthcare applications in the BHP inventory for nursing management. Method of Activity: In finding the root of the problem using fishbone diagrams, the scoring method was to prioritize issues to be resolved using SWOT Analysis. This community service was conducted in the Dhaha inpatient room of Gambiran Hospital, Kediri City with 22 medical and 2 non-medical personnel. Results: The application of lean healthcare in the Dhaha inpatient room, material management, pharmaceutical supplies, and household logistics was carried out continuously according to what nurses needed. However, after the implementation of lean healthcare, it begins with the implementation of 5S which regulates supplies according to patient needs, assigns items that are always used in patient services according to nurses every shift not every room, and puts or parks in places that are easy to reach. Efficient from inventory adjustments in the inpatient room in the form of Rp. 1,035,566. Discussion: The implementation of Lean Health Care